Rapid molecular test for tuberculosis: impact of its routine use at a referral hospital - Casela,Marilda (2018)
ABSTRACT Objective: To evaluate the impact of the use of the molecular test for Mycobacterium tuberculosis and its resistance to rifampin (Xpert MTB/RIF), under routine conditions, at a referral hospital in the Brazilian state of Bahia. Methods: This was a descriptive study using the database of the Mycobacteriology Laboratory of the Octávio Mangabeira Specialized Hospital, in the city of Salvador, and georeferencing software. We evaluated 3,877 sputum samples collected from symptomatic respiratory patients, under routine conditions, between June of 2014 and March of 2015. All of the samples were submitted to sputum smear microscopy and the Xpert MTB/RIF test. Patients were stratified by gender, age, and geolocation. Results: Among the 3,877 sputum samples evaluated, the Xpert MTB/RIF test detected M. tuberculosis in 678 (17.5%), of which 60 (8.8%) showed resistance to rifampin. The Xpert MTB/RIF test detected M. tuberculosis in 254 patients who tested negative for sputum smear microscopy, thus increasing the diagnostic power by 59.9%. Conclusions: The use of the Xpert MTB/RIF test, under routine conditions, significantly increased the detection of cases of tuberculosis among sputum smear-negative patients.